Effect of smoking on autonomic reflexes (Faculty of Medicine Universitas Indonesia, 2001)
Effect of cigarette smoking on autonomic reflexes was tested in 25 male smokers and compared with 25 age, sex matched non smokers. There was insignificant difference between heart rate (HR), blood pressure (BP) and other variables between non smokers and smokers (before smoking). But in smokers after cigarette smoking, the basal HR, basal BP (< 0.001), diastolic BP (p < 0.05) with change of posture (lying to standing), systolic BP (p < 0.01) on cold pressure test were all increased, while expiration: inspiration (E: 1) ratio (p < 0.01) and S: L ratio (p < 0.05) were reduced. These observations indicate acute rise in sympathetic traffic with someÂ effect on vagal activity. (Med J Indones 2001; 10: 95-7) Keywords : smoking, autonomic reflexes, sympathetic, vagus